Effects of total flavonoids of Rhizoma Drynariae on biochemical indicators of bone metabolism: a systematic review and meta-analysis - Li, Wei; Zhang, Zechen; Li, Yuyi; Wu, Zhenyu; Wang, Chengjie; Huang, Zhen; Ye, Baisheng; Jiang, Xin; Yang, Xiaolong; Shi, Xiaolin (Frontiers in Pharmacology, 2024)
Background: Evidence shows that the total flavonoids of Rhizoma Drynariae (TFRD) can improve bone mineral density (BMD). However, there is no evidence to summarize the improvement of biochemical indicators of bone metabolism (BIBM). Methods: The PubMed, Web of Science, Cochrane Library, Embase, Chinese National Knowledge Infrastructure (CNKI), Wanfang Database, Chongqing VIP Information Database (VIP) and SinoMed were searched from inception to May 6, 2024. The final included studies performed meta-analyses using RevMan 5.3. Results: Nine randomized controlled trials (RCTs) were ultimately included. The TFRD group had higher bone gla protein (BGP) and type I procollagen-N-propeptide (PINP) compared to the Other therapies (WMD: 5.11; 95% CI: 3.37, 6.84; p ＜ 0.00001; WMD: 13.89; 95% CI: 11.81, 15.97; p ＜ 0.00001). The tartrate-resistant acid phosphatase (TRACP) decreased significantly (WMD: -1.34; 95% CI: -1.62, -1.06; p ＜ 0.00001). The alkaline phosphatase (ALP) increased significantly (WMD: 7.47; 95% CI: 6.29, 8.66; p ＜ 0.00001). There were no significant differences in serum calcium (SC) or serum phosphorus (SP) levels between the TFRD and control groups (WMD: 0.08; 95% CI: -0.04, 0.20; p=0.17; WMD: 0.02; 95% CI: -0.02, 0.05; p=0.36). Conclusion: TFRD can stimulate bone formation and prevent bone resorption in osteoporosis (OP) patients, but it has no effect on SC and SP.